Development of technical education in the city of Kharkov: the contribution of Vikentii Khomych Gerburt-Geibovych - Gutnyk, Maryna (Київський національний університет ім. Т. Г. Шевченка, 2019)
The work of the leading scientist in the field of mechanics – Vikentii Khomych Gerburt-Geibovych is analyzed. He became one of those who, after the successful graduation from the Kharkiv Practical Technological Institute, stayed in this educational establishment as a teacher. In addition, his further activities contributed to the establishment of higher technical education in Ukraine. It should be noted that for a long time the name of this scientist was out of the attention of historians of science and technology. Therefore, taking into account the scientific work by V. Gerburt-Geibovych, as well as the using of archival materials, it is worthwhile the outlining of the results of the scientific activity of this scientist. Information about the future scientist's family is provided. In particular, it is stated that he was from a noble family. The talented graduate of KhPTI was invited to work at this educational institution. It is shown what subjects the scientist taught. Heredity in teaching the course of flour-mill production from the teacher – Professor K. Zworykin to the student – V. Gerburt-Geibovych was traced. The information about the probation of a scientist at the enterprises of Russian Empire is considered. V. Gerburt-Geibovych᾽s formation as a scientist is shown. For example in 1902 the scientist with Professor G. O. Latyshev, on behalf of the Kharkiv Agricultural Society, became one of the organizers of ploughs testing at Yankivsky Estate of the merchant P. I. Kharitonenko. In order to maintain an appropriate level of knowledge and exchange of information in 1909, the scientist visited the IX congress of flour mills and the 1st All-Russian flour-grinding exhibition held in St. Petersburg in the so-called "salt city". In 1911, the scientist was in a scientific trip in Germany, Switzerland, Belgium and Holland, where he inspected the several mills, elevators and factories that produced machines for mills. The activity of the scientist in the development of a new course of lectures – wood technology is analyzed. His research not only in the field of mechanics but also in botany is shown. The expert work of the scientist, including in the equipping of the salt-making plant and in the designing of mills, is shown. The activity of the scientist at the posts of the deputy chairman of the Student technical society and the chairman of the Committee for the needy students of KhTI are considered. Every month Academic Committee received a request from the students for material assistance. Funds for such payments were provided by citizens from all over the Russian Empire who arranged special evenings, performances for the students of the KhTI, some of them left the wills, where the estates departing in favor of students. The scientist had to consider applications, manage the distribution of funds and made reports. On the pages of "Proceedings of South Russian Association of Technologists" the reports about received funds were published: sponsors were indicated by name and the amount of donations. The information about cooperation of V. Gerburt-Geibovych with the Southern Russian Society of Technologists, the editorial office of the "Melnyk" magazine and the edition "People's Encyclopedia" was provided. In particular, in 1910, he published his articles "About the article A. M. Erlanger", "Effect on the quality of the flour of forced work of roller machines and prepacking", "About the needing of thorough separation of small impurities before the grain delivering to cockler". Next year, in the magazine "Melnyk", he published his article "About cooklers and methods of grain cleaning". It was shown that the scientist was one of the founders of women's polytechnic education in Ukraine. The presence of five daughters in the family became a significant incentive for Vikentii Khomych to open the Women's Polytechnic Institute in Kharkiv. The first years of functioning of this newly created institution are considered. It is alleged that wife of a scientist and one of the daughters graduated from the Women's Polytechnic Institute. In addition, in June 1919 Vikentii Khomych elected the vice-rector of the Kharkov Technological Institute. Emphasis is made on significant stress in the work, which led to a weakening of the scientist's health. Thanks to interviewing of relatives of the scientist, the year of his death was ascertained. Despite a rather short life course, only 48 years old, the scientist has left a distinctive mark in the history of the Kharkiv Technological Institute, which he graduated from. The memory of prominent ancestor remains among his descendants.

Аналізується доробок провідного ученого у галузі механіки – Вікентія Хомича Гербурт-Гейбовича. Подано відомості щодо родини майбутнього ученого. Вчений є випускником Харківського практичного технологічного інституту. Здібному випускнику було запропоновано працювати в цьому навчальному закладі. Показано які предмети викладав вчений. Простежено спадковість у викладанні курсу борошномельного виробництва від учителя - професора К. Зворикіна до учня – В. Гербурт-Гейбовича. Аналізується діяльність ученого щодо розроблення нового курсу лекцій – технологія деревини. Показані його дослідження не лише у галузі механіки, а й ботаніки. Стверджується що В. Гербурт-Гейбович також викладав й гідравліку. Розглянуто експертну роботу вченого, у тому числі щодо обладнання солеварного заводу та будівництва млинів. Розкрито діяльність науковця на посадах заступника голови студентського технічного товариства та голови комітету нужденним студентам ХТІ. Аналізується його внесок у ці організації. Подано відомості про співпрацю В. Гербурт-Гейбовича з Південноросійським товариством технологів, редакцією журналу "Мельник" та виданням "Народна енциклопедія". Підкреслено, що учений був одним із фундаторів Жіночого політехнічного інституту. Розглянуто перші роки функціонування цього новоствореного закладу. Акцентується увага на значній напруженості у роботі, що призвело до значного ослаблення здоров’я ученого. Завдяки інтерв’ювання родичів ученого відтворено рік його смерті.
Keywords: Kharkiv Practical Technological Institute; Women's Polytechnic Institute; flour-mill production; wood industry; People's Encyclopedia; Харківський практичний технологічний інститут; Жіночий політехнічний інститут; борошномельна промисловість; деревообробна промисловість; Народна енциклопедія